Interview of Lloyd Beebe by Brian Shoemaker - Beebe, Lloyd, 1916- (Byrd Polar Research Center Archival Program, 2005)
Erwin Verady, production manager for Walt Disney studio, pp. 11, 20 Walt Disney, filmmaker, p. 21 Roy Disney, filmmaker, pp. 21, 70 Admiral Richard E. Byrd, explorer, p. 27, George J. Dufek, pp. 31 Ches Wombley, weather forecaster for the Byrd Expedition, p. 37 Dr. Elrick, team physician, p. 45. Bob Stretch, Otter pilot, pp. 47-48, 52, 55 Max Keel, died in Antarctica, pp. 48-51, 53 Elmo Jones, Antarctic photographer for the Coast Guard, pp. 71-73 The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Lloyd_Beebe_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Lloyd_Beebe_2.mp3 Lloyd Beebe, the celebrated wildlife photographer, was born in 1916 in British Columbia, Canada, less than a mile from the American border. In later years, after some hesitation, he opted for American over Canadian citizenship. He grew up in Forks, Washington, a logging town, in the difficult years of the Great Depression. Money was scarce. Beebe dropped out of high school, and helped his father through logging, trapping, shooting cougars for the bounty, raising mink, and, after 1940, farming in Sequim, Washington. In time, this farm became the Olympic Game Farm. On the farm Beebe learned to appreciate and work with various animals, including elk, cougar, mink, bears, and others. As visitors came to photograph the animals, Beebe decided he might like to do the same. Thus, a career was born. Many of his early pictures were shots of a cougar in the wild. Actually it was a tame cougar that rode with Beebe in the front seat of his car. The cat stuck his head out the window like a dog, and got car sick like people. The success of the cougar pictures enabled the purchase of better equipment, and shots of wild elk and bear. In 1949 Beebe contacted the Walt Disney studio and he, and his wife, Catherine, were invited to visit. Some of his cougar pictures were used in the classic film, Vanishing Prairie, but more shots were needed for the film, so ...